One step derivatization and dispersive liquid-liquid microextraction of hydroxychloroquine sulfate for its sensitive and accurate determination using GC-MS - Bodur, Suleyman; Erarpat, Sezin; Gunkara, Omer Tahir; Bakirdere, Sezgin (ELSEVIER SCIENCE INC, 2022)
In the present study, a novel analytical method for the determination of hydroxychloroquine sulfate in human serum and urine samples was established. One step derivatization and dispersive liquid-liquid microextraction (DLLME) was developed for quantitative determination of hydroxychloroquine sulfate in aqueous samples. Hydroxychloroquine sulfate was first hydrolyzed and converted to its benzoate derivative by adding benzoyl chloride in chloroform which also served as extraction solvent. Significant parameters such as type/volume of extraction and dispersive solvents, concentration/volume of sodium hydroxide, type/period of mixing and concentration of derivatizing agent were carefully optimized by one variable at a time approach. Under the optimum DLLME conditions, limit of detection (LOD), quantitation (LOQ) and dynamic range were calculated as 35.2, 117.2 and 96-1980 mu g/kg (ppb), respectively. Recovery studies were conducted by spiked human serum and urine samples and the results were ranged between 93 and 107% with low standard deviations. Developed method can be easily used in hydroxychloroquine sulfate based SARS-CoV-2 and malaria treatment studies.
Keywords: Biological samples; Derivatization; GC -MS; Hydroxychloroquine sulfate; Microextraction; URINE SAMPLES; CHROMATOGRAPHY; EXTRACTION; PLAQUENIL; BLOOD; Pharmacology & Pharmacy; Toxicology